Penyimpangan ‘Iddah Perceraian Pada Masyarakat Gunung Meriah Aceh Singkil: Analisis menurut Perspektif Islam (Deviation of 'Iddah Divorce in The People of Gunung Meriah Aceh Singkil: An Analysis According to Islamic Perspective) - achyar, gamal; hasanah, hayatun (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
' Iddah is part of the sharia teaching, the implementation is obliged to the wives who are left by her husband, either left dead or left behind because of the divorce or Talak. In certain issues, found the practice of the ‘Iddah that happened to the community in the district of Gunung Meriah, District of Aceh Singkil. Where the implementation of the ‘iddah divorce is not executed in accordance with the provisions of the law of Islam, in particular there are two research questions in this article, namely; the first    deviation ‘iddah divorce on the community in the district of Gunung Meriah, District of Aceh Singkil. This research aims to know the form of irregularities ‘iddah divorce on the community in the district of  Gunung Meriah, District of Aceh Singkil and the second  review of Islamic law against ‘iddah divorce that is carried out on the community  in the district of  Gunung Meriah, District of Aceh Singkil. The research was conducted using a method of descriptive-analysis analysis. The results showed that the deviation  of ‘iddah  divorce on the community  in the district of  Gunung Meriah, District of Aceh Singkil there are three forms, namely;  accepting proposing to marriage from other people, leaving home without any need and emergency, using fragrance and dress up and the implementation of divorce ' iddah in the community  in the district of  Gunung Meriah, District of Aceh Singkil and about the  provision of ‘iddah in Islamic law. Islamic law through the understanding of the scholars on the evidence of Islamic law is a prohibition for women who are undergoing divorce, whether divorced or divorced to receive the banning of others, out of the house without any urgent need, and wear fragrances and dress up.